2019
DOI: 10.24275/uam/izt/dcbs/hidro/2020v29n3/cruz
|View full text |Cite
|
Sign up to set email alerts
|

Intra-annual variation of chlorophyll-a and nutrients in a hydraulically perturbed river-floodplain system in the Grijalva River basin

Abstract: Allometric growth and reduced pectoral fin regeneration rate in terrestrialized Polypterus senegalus Crecimiento alométrico y disminución de la capacidad de regeneración de la aleta pectoral en Polypterus senegalus terrestrizados

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…In the study area, TLCs showed the greatest variation in the concentrations of the three indicators, Chl-a, SD, and TP (Table 1), which was reflected in their proportionality overlap with PCL and IL. This amplitude in the variation of indicators in TCL has been related to seasonal flooding water that induces changes in the physicochemistry of water in temporary lakes in the Grijalva basin, the Amazon River, and the Poyang Lake floodplain [11,12,28]. However, the restricted temporal effect of flooding in the study area by the embankments reduced the expected seasonal variation of the water levels.…”
Section: Overlapping Of Water Quality Indicators In Three Surface Hyd...mentioning
confidence: 90%
See 4 more Smart Citations
“…In the study area, TLCs showed the greatest variation in the concentrations of the three indicators, Chl-a, SD, and TP (Table 1), which was reflected in their proportionality overlap with PCL and IL. This amplitude in the variation of indicators in TCL has been related to seasonal flooding water that induces changes in the physicochemistry of water in temporary lakes in the Grijalva basin, the Amazon River, and the Poyang Lake floodplain [11,12,28]. However, the restricted temporal effect of flooding in the study area by the embankments reduced the expected seasonal variation of the water levels.…”
Section: Overlapping Of Water Quality Indicators In Three Surface Hyd...mentioning
confidence: 90%
“…All samples were collected from 8:00 a.m. to 01:00 p.m. The four sampling times were established considering the expected water level changes in the Grijalva River [28,47].…”
Section: Samplingmentioning
confidence: 99%
See 3 more Smart Citations